Inclusive Education Through the Friendship Bridge Project - Ungureanu (Erdeli); Roman Alina Felicia (Babes-Bolyai University, 2023)
The Friendship Bridge project is an educational project born from the desire to remove some existing barriers between children, especially between children with special educational requirements and other children, from the desire to achieve the socialization of children with special educational requirements and the development of the associative capacities that determine the children to be able to live in permanent association with others, to be capable of friendly relations and, in particular, to want to maintain connections with their peers. The ongoing project since the fall of 2009 was initiated by the School Center for Inclusive Education No. 3 Oradea in the period 2009-2010, then by the School Center for Inclusive Education Orizont Oradea, in the period 2010-2013, the Teachers Training House of Bihor County in the school year 2013-2014, and the School Center for Inclusive Education No. 1 Oradea in the period 2014-2023. In this paper, we will make a retrospective of the activities carried out within the Friendship Bridge educational project identifying the role and importance of the projects in the integration and socialization of students with special educational requirements.